2012
DOI: 10.1007/s12640-012-9330-y
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Induction Between α-Synuclein and β-Amyloid in Adult Rat Neurons

Abstract: In spite of definite roles for β-amyloid (Aβ) in familial Alzheimer's disease (AD), the cause of sporadic AD remains unknown. Amyloid senile plaques and Lewy body pathology frequently coexist in neocortical and hippocampal regions of AD and Parkinson's diseases. However, the relationship between Aβ and α-synuclein (α-Syn), the principle components in the pathological structures, in neuronal toxicity and the mechanisms of their interaction are not well studied. As Aβ and α-Syn accumulate in aging patients, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…One of the first reports of recombinant alpha-synuclein seeding alphasynuclein aggregation in cortical neurons is that by Danzer et al (2009) in their study primary neuronal cultures are exposed to alpha-synuclein oligomers resulting on the accumulation of alphasynuclein inside the cells during the next 4 h. Exposure to in vitro generated alpha-synuclein fibrils has been shown to be toxic to hippocampus primary neurons (Volpicelli-Daley et al, 2011;Majd et al, 2013). Furthermore, these neurons have been used to show that pathological alpha-synuclein can be transmitted from cell to cell.…”
Section: Cellular Models Of Alpha-synuclein Pathology And/or Spreadingmentioning
confidence: 99%
“…One of the first reports of recombinant alpha-synuclein seeding alphasynuclein aggregation in cortical neurons is that by Danzer et al (2009) in their study primary neuronal cultures are exposed to alpha-synuclein oligomers resulting on the accumulation of alphasynuclein inside the cells during the next 4 h. Exposure to in vitro generated alpha-synuclein fibrils has been shown to be toxic to hippocampus primary neurons (Volpicelli-Daley et al, 2011;Majd et al, 2013). Furthermore, these neurons have been used to show that pathological alpha-synuclein can be transmitted from cell to cell.…”
Section: Cellular Models Of Alpha-synuclein Pathology And/or Spreadingmentioning
confidence: 99%
“…In the in vitro studies Aβ 42 was administered extracellularly was able to affect synuclein intracellularly, but the in vivo data was still lacking. Study performed in vitro in adult rat neurons by Majd et al [26] also showed the increase α-synuclein protein levels in the presence of Aβ 42 .…”
Section: Discussionmentioning
confidence: 92%
“…; Majd et al . ). Although Cdk5 is not responsible for the aberrant phosphorylation of neuronal ASN in AD, it is possible that this enzyme mediates the elevation of ASN protein level induced by Aβ.…”
Section: Does Cdk5 Promote Association Between Misfolded Proteins Commentioning
confidence: 97%
“…Previously it has been hypothesized that Ab and ASN mutually affect their accumulation and toxicity (Kallhoff et al 2007;Kazmierczak et al 2008;Bachhuber et al 2015). In vitro data indicated that subtoxic concentrations of Ab1-42 induce the significant increase in intra-and extracellular ASN levels in neuronal cells, as well as promote ASN aggregation in a cell-free system (Masliah et al 2001;Majd et al 2013). Although Cdk5 is not responsible for the aberrant phosphorylation of neuronal ASN in AD, it is possible that this enzyme mediates the elevation of ASN protein level induced by Ab.…”
Section: Does Cdk5 Promote Association Between Misfolded Proteins Commentioning
confidence: 99%
See 1 more Smart Citation